Intra-sector and inter-sector competition in a model of growth - Marco Di Cintio; Emanuele Grassi (Kiel Institute for the World Economy (IfW), 2015)
The role of patents is threefold: first, they are important to state the property rights of an invention; second, they are necessary to secure financing for starting a new venture; third, they are fundamental to recoup R&D investments. The main difficulty in preventing unauthorized use of an innovation is in the establishment of ranges and contexts of patents applicability. Noting the imperfections of the patent legal system, the authors are in a position to consider an economy with two levels of competition under different market structures: the inter-sector monopolistic competition and the intra-sector Cournot oligopoly. The explicit consideration of strategic interactions in a model of endogenous growth produces interesting results. Considering the sectorial market share as the indicator of patent system enforcement, the authors find that growth takes place, if and only if, there are some property rights of private knowledge produced by R&D activities. In turn, the patent system translates into a low degree of competition among firms. Its influence on the growth rate goes in a single unambiguous direction. As competition rises, few resources are available for R&D, so the growth rate goes down.
Keywords: E10; L13; L16; O31; O40; 330; product differentiation; endogenous growth; market structure; R&D